Pengaruh Iklim Organisasi, Kepemimpinan Otentik, Dan Knowledge Sharing Terhadap Perilaku Kerja Inovatif Pada Pegawai Biro Sumber Daya Manusia Kementerian Keuangan - Sintia, Eva; Partina, Anna (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This research is to determine the influence of organizational climate, authentic leadership and knowledge sharing on innovative work behavior of employees at the Human Resources Bureau of the Ministry of Finance. The research method used is a quantitative method, with a sample size of 170 respondents from a population of 297 employees. The data collection technique used in this research is distributing questionnaires, while data processing uses the SPSS 23 program. The analytical methods used include instrument testing, classical assumption testing, hypothesis testing and multiple linear regression testing. This research shows that organizational climate has a positive influence on innovative work behavior, authentic leadership has a positive influence on innovative work behavior and knowledge sharing has a positive influence on innovative work behavior. This research can pave the way for increasing employee readiness in facing global technological developments.